Heterogeneity of macrophage activation syndrome and treatment progression - Dong, Yuanji; Wang, Ting; Wu, Huaxiang (Frontiers in Immunology, 2024)
Macrophage activation syndrome (MAS) is a rare complication of autoimmune inflammatory rheumatic diseases (AIIRD) characterized by a progressive and life-threatening condition with features including cytokine storm and hemophagocytosis. Predisposing factors are typically associated with microbial infections, genetic factors (distinct from typical genetically related hemophagocytic lymphohistiocytosis (HLH)), and inappropriate immune system overactivation.Clinical features include unremitting fever, generalized rash, hepatosplenomegaly, lymphadenopathy, anemia, worsening liver function, and neurological involvement. MAS can occur in various AIIRDs, including but not limited to systemic juvenile idiopathic arthritis (sJIA), adultonset Still's disease (AOSD), systemic lupus erythematosus (SLE), Kawasaki disease (KD), juvenile dermatomyositis (JDM), rheumatoid arthritis (RA), and Sjögren's syndrome (SS), etc. Although progress has been made in understanding the pathogenesis and treatment of MAS, it is important to recognize the differences between different diseases and the various treatment options available.This article summarizes the cell types and cytokines involved in MAS-related diseases, the heterogeneity, and treatment options, while also comparing it to genetically related HLH.